Selective synthesis of N-unsubstituted and N-arylindoles by the reaction of arynes with azirines - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; "Jain, Shailja"; Gonnade, Rajesh G.; Biju, Akkattu T. (Journal of Organic Chemistry, 2016)
The transition-metal-free and temperature-dependent highly selective reaction of arynes with 2H-azirines allowing the synthesis of either N-unsubstituted or N-arylindoles has been developed. At 60 degrees C, arynes generated from 2-(trimethylsilyl)aryl triflates smoothly insert into 2H-azirines to form 2,3-diarylindoles with high selectivity. Interestingly, when the reaction was performed at -10 degrees C, the selectivity was switched to the formation of 1,2,3-triarylindoles in good yields.

Synthesis of functionalized amino epoxides by a three-component coupling involving aziridines, arynes and aldehydes - Roy, Tony; Thangaraj, Manikandan; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2016)
A transition-metal-free three-component coupling involving N-substituted aziridines, arynes and aldehydes resulting in the formation of trisubstituted N-aryl alpha-amino epoxides has been demonstrated. The reaction likely proceeds via the highly strained cyclic nitrogen ylide intermediates generated from aziridines and arynes.

Synthesis of functionalized β-keto arylthioethers by the aryne induced [2,3] Stevens rearrangement of allylthioethers - Thangaraj, Manikandan; Gaykar, Rahul N.; Roy, Tony; Biju, Akkattu T. (Journal of Organic Chemistry, 2017)
A mild and transition-metal-free synthesis of β-keto arylthioethers has been developed by the aryne triggered [2,3] Stevens rearrangement of allylthioethers. The key sulfur ylide intermediate for the rearrangement was formed by the S-arylation of allylthioethers with arynes generated from 2-(trimethylsilyl)aryl triflates using CsF. Later, the reaction products are converted into valuable heterocycles in two steps.